Secured one-handed multi-modal wireless interface for robotic applications in an industrial environment - Wei, Lin Yun (2015)
Robots have an increasing demand and importance in industrial applications. Industrial robots are employed to replace humans in performing dangerous, hazardous, tedious or repetitive tasks, by which reduced the physical and cognitive workload of humans in industrial applications. Distinct from an ordinary office set-up, industrial robot operators are exposed to a different working environment. Hand movements may be restricted by Personal Protective Equipment, such as gloves. When gloves are worn, accuracy of pressing small buttons or touch-screen devices would significantly decrease. Studies have shown that, if the reliability of human robot interface is not sufficient, workload of human operators would not be effectively reduced. Thus, it is necessary to have properly designed interface for Human Robot Interaction. It is desired by operators to adopt natural ways for Human Robot Interaction. Accelerometers and gyroscopes are fast becoming popular in gesture recognition, due to their low cost, low power consumption and portability. Prototype of a portable one-handed robot controller utilizing a Human Robot Interface with two selectable modalities and wireless connection were designed, tested and evaluated, both in a simulated environment and with practical robot applications. The hardware design was light and intuitive. Based on experiments, users could master the interface in a short period of time. Both modalities of interface were proven to be effective and accurate, having their own advantages in different practical applications. Possible future implementations were also proposed in the report.